Screening for TBX1 Gene in Children With or Without Microdeletion of Chromosome 22q11 and Conotruncal Defect. Issue 2 (18th September 2015) - Anilkumar, Alka; Kappanayil, Mahesh; Nampoothiri, Sheela; Thampi, M.V.; Vasudevan, D.M.; Kumar, R. Krishna
Abstract : Objective: In order to understand the role of the TBX1 gene in humans, Indian children with or without a microdeletion of chromosome 22q11 and conotruncal defects were screened by fluorescent in situ hybridization (FISH) using a TBX1 commercial probe. Methods: All patients were tested with commercial FISH probes on chromosome 22q11. Besides these, the deletion of the distal arm of chromosome 10 was analyzed, and phenotypic features were also taken into consideration. Results: A comparable result showing 22q11 deletion was obtained using the 3 probes (TBX1, TUPLE1, and N25) from the chromosome 22q11 region. Conclusion: The study confirms the role of contiguous genes including TBX1 in the pathogenesis of conotruncal defects. It also indicates that in a routine clinical practice either of the FISH probes (ie, TUPLE1, N25 or TBX1) can be used to detect 22q11 deletion. Such genetic testing is important, since patients with 22q11 deletion need early medical intervention based on associated symptoms.